(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
Islamic economics represents a value-based economic framework derived from Islamic teachings, aiming to establish justice, equity, and social welfare in economic activities. Unlike conventional economic systems that primarily focus on profit maximization, Islamic economics integrates moral, ethical, and social considerations into economic decision-making. This article examines the importance of Islamic economics in addressing contemporary economic challenges such as inequality, financial instability, poverty, and ethical degradation. Through an analytical and conceptual approach, the study highlights the fundamental principles of Islamic economics, its role in promoting social justice, financial stability, and sustainable development, and its relevance in the modern global economy. The findings suggest that Islamic economics provides a viable and ethical alternative to conventional economic models.